MD Voldemar Sumberg and the Folk Medicine Collection of the Estonian Museum of Hygiene from the 1920s and 1930s - Ave Tupits (Journal of Ethnology and Folkloristics)
Based on the documents preserved in several museums and archives in Tartu and Tallinn (the Estonian Health Care Museum, the Estonian State Archives, the Estonian Historical Archives, the Estonian Folklore Archives and the Estonian National Museum), the article will give an overview of the views of the director of the Estonian Museum of Hygiene, Voldemar Sumberg, on the relationship between folk medicine and modern medicine; the data on folk medicine collecting campaigns with Sumberg's involvement in the 1920s; and the fate of the folk medicine records and items collected by the Museum of Hygiene during the 1920s and 1930s, according to the documentation and archival material found so far.